Climate change in Cambodia, Philippines and Vietnam a vulnerability analysis at the commune and household levels - The, B. D.; Mendoza, M. E. T.; Naret, H. (2003)
The study discussed the vulnerability analyses of the commune and household levels of selected provinces in Cambodia, Philippines and Vietnam particularly those located in the lowland and coastal areas with relatively high poverty incidence , large areas of land devoted to agriculture, and poor social infrastructure facilities. Vulnerabilities were assessed considering the spatial and social dimension (exposure, sensitivity and adaptive capacities) using participatory approaches. the study found out the following contributors to climate change vulnerabilities: 1) For Laguna, Philippines: sensitivity and low adaptive capacity (e.g., unpreparedness, fragile location, lack of amenities, limited information on climate change and its impacts); 2) For Thua Thien Hue, Vietnam: high exposure to hazard, low adaptive capacity was , and lack of long term planning perspective on adaptation and 3) For Kampong Speu, Cambodia: low adaptive capacity was identified as the dominant determinant to vulnerability. Vulnerabilities to climate change well likewise found to differ across local contexts. Vulnerability was found to be gender differentiated at three sites. Women were move vulnerable to climatic hazard than men due to the fact that women were not as physically strong as men, have limited skills and opportunities, but have more responsibilities in taking care of family members. While demand for effort and participation in the productive sphere went up for both men and women during response and rehabilitation periods, there was no increase in demand for men to participate on the domestic front except for the rebuilding of physical structures. However, in general , the elderly and the children, disabled, women and women-headed households, and poor people were more vulnerable.
Keywords: Climate change